The relationship of attitude, subjective norms, trust and intention to use halal cosmetic products at public institutions of higher learning in Malaysia - Romle, Abd Rahim; Mohd Udin, Mashitah; Abu Seman, Nurul Hamimah; Ismail Bakri, Ilman Nabil; Nordin, M Shahadat Ali; Mohd Zaya, Ummi Hidayah (ISLAMIC WORLD Network for Environmental Science and Technology (IWNEST Publisher), 2016)
Background: Halal branding is not a new issue in the halal market.Even though it still in the early stages for some products, it is well known that branding has a good.Besides that, the application of brand theory unnecessarily restrict to the term of halal and the interpretation of its meaning and overall concept of halal in Islam.Halal conscious customers have a high regard for halal concept, and they tend to use behavioral traits decision making.Therefore, the purpose of this study is to examine empirically the relationship between attitude, subjective norms, trust and intention to use Halal cosmetics products among students at public institutions of higher learning in northern region Malaysia.The respondents of this study are 327 students in various backgrounds.The data were analyzed through descriptive analysis, ANOVA, T-test, Pearson Correlation and Multiple Regressions by using SPSS version 19.0.Suggestion for further research and recommendation for the decision makers have been forwarded.